Věněk Šilhán: Muž, který držel v ruce moc i lopatu - Čížková, Martina (Lidé města, 2005)
Roots, authority, morals, and culture – four words as four supporting pillars of Professor Věněk Šilhán’s life. Man who held reins of power, as well as a shovel in his hands; just an extreme version of fate of many thousands of people in this country. Fate as a seesaw where one faces a wayward adversary in form of politics. Just as many others after the war, young and zealous Věněk believed in brighter future, only to get sober in 1968 when he was a well respected director of an institution. Year 1968 was crucial in his life. He suddenly entered the world of high politics as the first secretary of the extraordinary, so called Vysočany assembly of the Czechoslovak Communist Party. Even thought he carried out this function for only a few days it was to determine his future life.